Response of Oil Palm Seedlings Planted on Highly Weathered Acid Soils to Magnesium Fertilizers - Mohamad, Azham (2003)
Magnesium (Mg) is an important nutrient for oil palm growth and Mg fertilization is recommended during immature stage to ensure no early growth limitation. Most Malaysian acid soils are low in exchangeable Mg and inadequate for optimum plant performance. This study was conducted to evaluate the effect of Mg fertilization on the growth of oil palm seedlings using two types of Mg fertilizers; kieserite and CIMA-Mg (a local synthetic industrial Mg sulphate). Two studies were carried out, a nursery experiment with two types of acid soils and a nutrient solution experiment. In both studies, the growth of oil palms seedlings was evaluated by recording plant height, trunk girth, and plant tops and roots dry weight. Chlorophyll content in fronds number 3 and 9 were measured using chlorophyll meter SPAD-502. Nutrient tissue analysis was performed to determine the concentrations of magnesium (Mg), phosphorus (P), potassium (K) and calcium (Ca) in fronds number 3 and 9. Analysis of total and exchangeable Mg in soil was also conducted to determine the Mg status of the soil after the experiment. In both experiments, oil palm fertilized with Mg showed a significant increased in trunk girth, plant top and root dry weight when compared to control. Magnesium deficiency symptom was observed at the age of 8 months in nutrient solution experiment, while 10 months in acid soils. The symptom was observed in frond number 9 with the reading of chlorophyll content dropped to 22.90 SPAD at the time of harvesting. The critical value for chlorophyll content in frond number 9 was 42.78 SPAD. All palms treated with Mg fertilizers had Mg concentrations in frond number 9 ranged between 0.28% - 0.34% for nursery experiment and 0.22% - 0.34% for nutrient solution experiment. The mean concentrations of Mg in frond number 9 for control palms were between 0.03% - 0.08%. An antagonistic effect was observed between Mg and both K and Ca in all experiments. However, the synergistic effect between Mg and P was only observed in the nursery experiment but not obvious in the nutrient solution experiment. Both soils treated either with kieserite or CIMA-Mg was rated as relatively sufficient in term of exchangeable Mg status except for Prang series fertilized with kieserite that was rated as relatively high. In soils fertilized with kieserite, most of the Mg was in the exchangeable form, 178 ug Mg kg-1 and 412 ug Mg kg-1 for B ungor and Prang series soil, respectively, while for soil treated with CIMA-Mg were 126 ug Mg kg-1 for Bungor series and 196 ug Mg kg-1 for Prang series soil. The study suggested that both kieserite and CIMA-Mg were suitable as a source of Mg fertilizers in oil palm nursery to supply Mg for the growth of the seedlings. The Ca content present in the CIMA-Mg, probably help to improve root proliferation especially during the early growth of the oil palm seedlings.